2001
DOI: 10.1001/archinte.161.8.1065
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Oral Contraceptive Use and the Risk of Myocardial Infarction

Abstract: Current use of low-dose OCs in the United States is unrelated to an increased risk of MI among nonsmokers and light smokers, but users who smoke heavily may be at greatly increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…It is worth noting that the published case the only associated risk factor was smoking. There is a study use of low dose (≤50 µg) estrogen is unrelated to an increased risk of MI among light smokers (≤24 cigarettes/day) , whereas, some studies showed, regardless of the type of OC, an increased events of arterial thrombosis, mainly MI and stroke, in smokers . Our preliminary results are similar to those previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…It is worth noting that the published case the only associated risk factor was smoking. There is a study use of low dose (≤50 µg) estrogen is unrelated to an increased risk of MI among light smokers (≤24 cigarettes/day) , whereas, some studies showed, regardless of the type of OC, an increased events of arterial thrombosis, mainly MI and stroke, in smokers . Our preliminary results are similar to those previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Over the last few decades, several small case-control studies have reported on the increased risk of MI associated with use of oral contraceptives, heavy smoking, history of diabetes and hypertension in younger women 2, 3, 2325 . From a dietary perspective, the only available case-control data suggest a reduction in risk with moderate alcohol consumption and a modest increase in risk with very high coffee intake (≥ 10 cups per day) 26, 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is limited evidence regarding associations between modifiable lifestyle factors and CHD in young women. Existing evidence for CHD risk factors in young women comes primarily from small case-control studies and is limited to oral contraceptive use (24), smoking (25), diabetes (25), hypertension (25), alcohol (26), and coffee (27). …”
Section: Discussionmentioning
confidence: 99%